2019
DOI: 10.1108/jpbm-10-2018-2068
|View full text |Cite
|
Sign up to set email alerts
|

Converting internal brand knowledge into employee performance

Abstract: Purpose Internal branding efforts are essential in improving employee performance in services marketing. Drawing on reformulation of attitude theory, this paper aims to contribute to the internal branding literature by positing that while internal brand knowledge (IBK) is essential for transforming brand vision into brand reality, it is not brand knowledge per se but its integration with other brand- and customer-related aspects that drive superior employee performance. In particular, this paper develops a cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 96 publications
4
37
0
1
Order By: Relevance
“…Our model of the direct and indirect influence of service climate explains 63% of BCB's variance, providing evidence that it is a most effective means to enhance employee BCB. Although other approaches such as internal branding practices (Baker et al, 2014;Chang et al, 2012;Ngo et al, 2019;Nguyen et al, 2019) may provide additional explanation on the variance of BCB, our findings indicate that the integration of both social exchange and social identity are crucial to explain this variance. We further found that the influence of service climate on hotel employee BCB is likely to vary according to employees' power distance orientation.…”
Section: Contributionsmentioning
confidence: 63%
“…Our model of the direct and indirect influence of service climate explains 63% of BCB's variance, providing evidence that it is a most effective means to enhance employee BCB. Although other approaches such as internal branding practices (Baker et al, 2014;Chang et al, 2012;Ngo et al, 2019;Nguyen et al, 2019) may provide additional explanation on the variance of BCB, our findings indicate that the integration of both social exchange and social identity are crucial to explain this variance. We further found that the influence of service climate on hotel employee BCB is likely to vary according to employees' power distance orientation.…”
Section: Contributionsmentioning
confidence: 63%
“…Internal marketing literature demonstrates the effect of internal branding practices on employee brand knowledge, brand identification, brand understanding, as well as their commitment and brand-supporting behavior (e.g., Morhart et al 2009 ; Löhndorf and Diamantopoulos 2014 ; Ngo et al 2020 ; Piehler 2018 ; Piehler et al 2016 ). A key role in this aspect relates to knowledge dissemination to transfer brand meaning and to deliver the brand promise.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…A key role in this aspect relates to knowledge dissemination to transfer brand meaning and to deliver the brand promise. Internal brand knowledge is defined as “cognitive activity upon which employees understand, remember, make decisions, and perform based on the information they have received” (Ngo et al 2020 , p. 275). Further, brand knowledge contributes to one’s brand understanding―that is, employees’ comprehension of brand-related information (Piehler 2018 ; Piehler et al 2016 ).…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations